"How Emotional Do I Make It?": Making a Stance in Multimodal Compositions. Issue 6 (10th January 2020) - Rowsell, Jennifer
Abstract: For literacy educators, there is a need to understand students' pathways into composition and mediate contemporary, multimodal compositional pathways with more academic ones. In an effort to mediate between middle and high school students' schooling and curricular demands and their everyday interests and investments in media and communicational systems, the author offers educators a way to frame composition that attends to the potential and affordances of multiple modes of expression and representation. Combining affect theory with Arendt's writings on thinking and embodiment, the author presents a research study with adolescents who made stances in selfies, self‐portraits, and written artist statements that are indicative of new rhetorical and compositional practices. Stance, as a construct in modern compositions, represents the ways that young people interface with ideas and experiences within the world that materialize in and animate their designs. Stance provides young people with a space to tell the stories they want to tell through media and mediums of their choosing.